Esensi Pengendalian Internal Pada PT XYZ Otomotif Dalam Perspektif Fenomenologi - Al Salam, Faris; Anwar, Choirul; Khairunnisa, Hera (Jurnal Akuntansi, Perpajakan dan Auditing, 2024)
This research was conducted with the aim of exploring internal control at XYZ automotive company in general administration department. The sampling technique in this research used purposeful sampling that consist of four informants. This research uses a phenomenological approach using John W. Creswell's research design which focuses on narrative research exposure in proposing the application, effectiveness and meaning in internal control. The results of this study demonstrates that effective internal control requires integrity, consistency, transparency, proper risk assessment, effective communication and continuous monitoring. Key factors are people, technology and KPIs, with benefits in efficiency, effectiveness and maintaining the company's reputation. The main challenges are resistance to change, communication, technology and law. The values of integrity and professionalism are important for consistent internal control.